2007
DOI: 10.1039/b610284k
|View full text |Cite
|
Sign up to set email alerts
|

High sequence-coverage detection of proteolytic peptides using a bis(terpyridine)ruthenium(ii) complex

Abstract: The use of a bis(terpyridine)ruthenium(ii) complex for peptide labeling (Ru-CO labeling) supplied high intensity peaks in mass spectrometry (MS) analysis that overcame the contribution of protonation or sodiated adduction to peptides. Ru-CO-labeled insulin A- and B-chains were detected simultaneously in comparable peak abundance by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). The mass spectra of chymotryptic peptide fragments of Ru-CO-labeled insulin also simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Sequence coverage was calculated by dividing the number of amino acids observed by the number of amino acids in the entire sequence. Naturally, high protein sequence coverage thus has a higher confidence than a low sequence coverage . This forms the interpretation of diverse transition patterns of sequence coverage with pronase.…”
Section: Biophysical and Biological Relevance‐based Target Validationmentioning
confidence: 99%
“…Sequence coverage was calculated by dividing the number of amino acids observed by the number of amino acids in the entire sequence. Naturally, high protein sequence coverage thus has a higher confidence than a low sequence coverage . This forms the interpretation of diverse transition patterns of sequence coverage with pronase.…”
Section: Biophysical and Biological Relevance‐based Target Validationmentioning
confidence: 99%
“…Interestingly, Keyes et al developed ruthenium(II) polypyridyl luminophores anchored to peptide sequences as a new class of stimulated emission depletion (STED) microscopy probes for the imaging of key cell organelles . Ueyama et al also described a peptide‐labeling approach by using Ru II terpyridine complexes to implement the mass spectrometry detection of proteolytic peptides …”
Section: Introductionmentioning
confidence: 99%
“…[26] Ueyama et al also described a peptide-labeling approach by using Ru II terpyridine complexes to implement the mass spectrometry detection of proteolytic peptides. [27] As far as it concerns RGD-type peptides, only a few examples are described. Thus, Sadler et al reported the synthesis of a Ru II arene complex attached to the linear RGD tripeptide [28] that dissociated from the peptide by irradiation with visible light to form an aqua complex that generated monofunctional adducts with the guanine bases of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The widely applied method of ''bottom-up'' proteomics by peptide analysis via MS of a tryptic digest does not provide 100% coverage of the protein [14][15][16]. Although this method is well established and has been an indispensable tool in the proteomics field, it is difficult to determine modifications made to the mature protein when compared with the sequence that is predicted from the open-reading frame [17].…”
Section: Introductionmentioning
confidence: 99%